ANALISIS PERMASALAHAN BADAN USAHA MILIK DESA (BUM DESA) DI KABUPATEN BENGKALIS - Dewi Junita; Oetary Triyani; Yulia Safitri; Yolanda Safitri Nelaz (Awal Bros Journal of Community Development, 2024)
Village-Owned Enterprises (BUM Desa) are business institutions engaged in the management of village economic assets and resources within the framework of village community empowerment. BUM Desa is established by the village and/or together with villages to manage businesses, utilize assets, develop investment and productivity, provide services, and/or provide other types of businesses for the greatest welfare of the village community. Thus, the government and community's hopes for the growth of the village economy and community welfare are attached to BUM Desa. In Riau Province, all villages in Riau have BUM Desa, namely 1,591 villages. Bengkalis Regency already has BUM Desa with a total of 136 BUM Desa units. Bengkalis Regency, with its wealth of natural resources and abundant economic potential, has a great opportunity to develop diverse and innovative BUM Desa. However, there are still various problems that hinder its development and sustainability. Some of these problems include lack of human resource capacity, limited capital, ineffective management, and limited access to markets and technology. Overcoming these problems requires comprehensive and sustainable efforts. The purpose of this community service activity is to provide training in analyzing financial reports of Village-Owned Enterprises in Bengkalis Regency to identify root problems and find practical and applicable solutions. Through this community service activity, it is hoped that mentoring, training, and empowerment can be carried out for Village-Owned Enterprise managers and village communities so that they are able to optimize their potential and resources. This community service activity has been carried out in Bengkalis Regency. The participants in this activity are Village-Owned Enterprise Operational Executors, namely 14 Operational Executors from 14 Village-Owned Enterprises in Bengkalis.